Representasi Pelecehan Seksual Dalam Konsep Film Horor Religi Pada Film Qorin (2022) - Rivanda Daffauzan Thaufani; Sa'idah, Zahrotus (Institut Nalanda, 2024)
The development of horror films in Indonesia continues to demonstrate innovation over time. One significant example is the film